Growth Rhythm and Individual Models of Wine Bamboo Plantation, Oxytenanthera braunii / 酒竹的个体生长发育规律及其相关模型 - 李伟成; 王树东; 钟哲科; 盛海燕; 周妍 (Forest research (Beijing), 2011)
The authors studied the shoot growth rhythm of wine bamboo, Oxytenanthera braunii, which is of great economic importance in Tanzania and has been introduced to China recently. And also, individual-based model was used to delineate and capture the essence of the shoot growth system well enough addressing specific characteristics of parameters about the system. The results showed that the power function could be used to set up the relationship between leaf number and node number, which was the same as branch number after truncating. Compensation effect of mother individuals after transplanting was important for wine bamboo adapting to the semi-arid area in southwest China. The quadratic function could be used to express the relationship between the number of residual nodes with branch and the percentage of branch number contributing to the total number of the individual without truncating which was also shown by the percentage of leaf number. The probability distribution function such as Weibull and Gamma were